2000
DOI: 10.1021/ci990222k
|View full text |Cite
|
Sign up to set email alerts
|

QSAR Treatment of Electronic Substituent Effects Using Frontier Orbital Theory and Topological Parameters

Abstract: A methodology for the estimation of Hammett substituent constants from computational-based descriptors utilizing quantitative structure activity/property relationships (QSAR/QSPR) formalism is presented. Electronic descriptors derived from quantum chemical calculations and molecular topology were used to generate computational-based analogues of empirical Hammett substituent constants from statistical analysis. Global quantum chemical reaction indices were drawn from frontier orbital theory and density functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 70 publications
0
19
0
1
Order By: Relevance
“…This approach has the advantage that the overall electronic contribution of the substituent ensemble is captured in an unbiased manner, and that potential steric effects specific to the pyrazoline fluorophore architecture can be later evaluated on the basis of the LFER. A number of studies showed that several quantum chemical parameters linearly correlate with experimentally derived Hammett constants 18,2429. Recently, Galabov et al demonstrated that the theoretical electrostatic potentials at the nuclei (EPN) of carbon atoms in substituted benzenes represent an excellent reactivity descriptor 30.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has the advantage that the overall electronic contribution of the substituent ensemble is captured in an unbiased manner, and that potential steric effects specific to the pyrazoline fluorophore architecture can be later evaluated on the basis of the LFER. A number of studies showed that several quantum chemical parameters linearly correlate with experimentally derived Hammett constants 18,2429. Recently, Galabov et al demonstrated that the theoretical electrostatic potentials at the nuclei (EPN) of carbon atoms in substituted benzenes represent an excellent reactivity descriptor 30.…”
Section: Introductionmentioning
confidence: 99%
“…For example, partial charges, Highest Occupied Molecular Orbital (HOMO) and Lowest Occupied MOlecular Orbital (LUMO) energies are commonly evaluated using semiempirical methods, while Eroglu and Turkmen [29] described density functional theory (DFT) derived descriptors such as electronegativity, hardness and ionization potential (though Puzyn et al question the need for such a high level of theory [30]). Sullivan et al [31] employed frontier orbital theory and DFT to generate quantum mechanical analogs of Hammett substituent constants [32] and showed that they agreed well with empirically derived constants.…”
Section: Numerical Descriptorsmentioning
confidence: 88%
“…For example, partial charges, Highest Occupied Molecular Orbital (HOMO) and Lowest Occupied MOlecular Orbital (LUMO) energies are commonly evaluated using semi-empirical methods, while Eroglu and Turkmen [29] described density functional theory (DFT) derived descriptors such as electronegativity, hardness and ionization potential (though Puzyn et al question the need for such a high level of theory [30]). Sullivan et al [31] employed frontier orbital theory and DFT to generate quantum mechanical analogs of Hammett substituent constants [32] and showed that they agreed well with empirically derived constants.…”
Section: A Categorization Of Descriptorsmentioning
confidence: 99%